Political Hegemony of the New Order Government in Papua in Poetry in Indonesia (Gramsci's Literature Sociology Study) - Hardyansah, Hangga Eko; Nurhadi, Nurhadi (East Asian Journal of Multidisciplinary Research, 2024)
This research examines Indonesian poetry which reflects the socio-political dynamics of Papua during the New Order era, using the lens of literary sociology and Antonio Gramsci's theory of hegemony. Through a hermeneutic approach, the analysis of selected poems shows how literature functions as a tool of resistance to political hegemony, reflecting the struggle for identity and aspirations for social justice in Papua. This research found that poetry is an effective medium for articulating resistance, challenging dominant narratives, and voicing the socio-political injustices faced by the Papuan people. The results of this research provide an important contribution to the understanding of the role of literature in a socio-political context, demonstrating its potential as a tool for socio-political change and inspiring a new understanding of the dynamics of resistance and hegemony.